Detection assay of polymyxin resistance coding mcr-1 gene based on CRISPR/Cas13a system - Song, Yingjie; Hu, Qiang; Han, Yao; Liu, Hongbo; Huang, Zhenyang; Niu, Mengwei; Dong, Xue; Yan, Kuocheng; Jin, Li; Li, Hao; Sun, Yansong (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionPolymyxins are reserved as an ultimate defense against multidrug-resistant bacteria. The emergence of the polymyxin resistance gene mcr-1 poses a potential risk for the treatment of severe infections caused by Gram-negative bacteria. Timely detection and monitoring the mcr-1 gene are essential for guiding anti-infective therapy and controlling the spread of polymyxin resistance. Quantitative real-time PCR (qPCR) is one of the common methods for detecting resistance genes. However, qPCR has equipment dependency, and is not feasible in primary healthcare settings. Currently, there remains a lack of a highly sensitive and portable method for detecting the mcr-1 gene.MethodsWe established and optimized detection assays of the mcr-1 gene based on CRISPR/Cas13a system and lateral flow strips. The detection method was preliminarily evaluated using clinical isolates from Escherichia coli, compared with qPCR.ResultsThe method for detecting the mcr-1 gene based on the CRISPR/Cas13a system and lateral flow strips was established, with a detection limit of 100 copies/mL. This method demonstrated high analytical specificity, with no cross-reactivity detected in non-mcr-1 and non-resistant strains. Among 36 clinical isolates, the method identified 31 strains as positive for the mcr-1 gene, and had a 100% concordance rate with the results of qPCR.ConclusionsWe established a detection method for the polymyxin resistance mcr-1 gene based on the CRISPR/Cas13a system. This method enables visual readouts without instruments, making it potentially applicable to primary healthcare settings and field surveillance.